Willingness to pay for informal care in France: The value of funding support interventions for caregivers - Chloé Gervès-Pinquié; Martine M. Bellanger; Joel Ankri (Health Economics Review, 2014)
Objectives: This article aims to assess the relationship between the monetary value of informal care - approximated with the caregiver's willingness to pay to reduce caregiving time - and the caregiver's need of three types of support services: care training, respite care and support group. Developing such services may be the only way to provide sustainable informal care in the future, along with efficient allocation. Data & Methods: Data used stemmed from two representative national surveys conducted by French National Institute of Statistics and Economic Studies and the French Head Office of Research, Studies, Evaluation and Statistics of the Social Affairs Ministry in 2008. The contingent valuation method was used to approximate the monetary value of informal care. The model was run on 223 informal caregivers of people with Alzheimer's Disease. Statistical analyses were performed using Heckman's two-step estimation strategy, which is known to correct selection bias. Results: On average, one hour of informal care was estimated at exteuro12.1. Monetary value of informal care was influenced by the caregiver's need of care training (p<0.01). No similar association was found for respite care or support group. Discussion: Since informal caring value increases with caregivers' need of care training, improving caring skills and capabilities through training support is likely to improve its benefits.
Keywords: 330; Support services; Care training; Contingent valuation; Informal care; Alzheimer's Disease